Giant Cell Lung Carcinoma: A Case Report of a Rare Histology Type of Non-Small Cell Lung Cancer - Putri, Kadek Sri Adi; Kusumawardani, Ida Ayu Jasminarti Dwi; Sriwidyani, Ni Putu; Komalasari, Ni Luh Gede Yoni (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Giant cell carcinoma (GCC) of the lung is a subtype of lung cancer, undifferentiated non-small cell carcinoma, in which there are no features of small cell carcinoma, adenocarcinoma, or squamous cell carcinoma. Due to its aggressive clinical manifestations and peculiar pathological features, GCC of the lung is a highly anaplastic variant of bronchogenic carcinoma. Case: A 45-year-old woman was clinically suspected of having a lung malignancy, and a biopsy of the right lower lobe pleura and parietal pleura was performed. The histopathology showed hypercellular tumor cell clusters, forming a syncytia-like sheet pattern. Tumor cells were pleomorphic and contained many giant cells that confirmed the diagnosis of GCC. The patient was diagnosed with GCC of the lung, stage IVB, Karnofsky scores 50-60% with malignant pleural effusion, peritoneal metastases, bone metastases, and grade 3 malignant ascites with bacterial peritonitis. The patient passed away due to septic shock caused by bacterial peritonitis. GCC of the lung is one of the aggressive types of lung cancer. GCC has an unusual tendency to metastasize to the gastrointestinal tract. In this case, the patient had an enlarged abdomen since it was known that she had a malignancy that had continued to grow. From the ascitic fluid analysis, a carcinoma was found to be seeding. Conclusion: The prognosis of GCC of the lung is generally poor. Our case was diagnosed with GCC of the lung that had already spread to the bone, peritoneal, and had grade ascites. The patient's survival rate was generally poor, and she passed away due to bacterial peritonitis without having received any therapy for her cancer.